Plenary Conference 1: From the lab to outside. Lessons from nature - Echeverri López, Luis Fernando (Revista Productos Naturales, 2022)
In addition to the fact that Natural Product Chemistry is well suited to do extensive basic research, it undoubtedly generates molecules in addition to structural and biological information to solve various human problems, especially in the pharmacological field, agriculture, cosmetics, food, and other industrial applications...